Early initiation of Dapagliflozin and its effect on health related quality of life in acute heart failure: a randomised controlled trial - Fatima Gilani, Syedah Fauzia; Ali, Dr. Shabana; Farhat, Dr. Kulsoom; Noor, Dr. Mudassar; Siddique, Dr. Muhammad Bilal; Waqar, Dr. Farzana (Journal of the Pakistan Medical Association, 2024)
Objective: To determine the role of dapagliflozin in improving functional status and health-related quality of life in acute heart failure cases. Method: The prospective, randomised controlled study was conducted from July 2022 to January 2023 at the Pharmacology Department of Army Medical College, National University of Medical Sciences, Rawalpindi, Pakistan, in collaboration with the Armed Forces Institute of Cardiology, Rawalpindi, and comprised hospitalised adult patients of either gender with acute heart failure. They were randomised into two equal groups, with intervention group A receiving oral dapagliflozin 10mg daily in addition to conventional therapy, and with control group B receiving conventional therapy alone. Health-related quality of life was assessed using Kansas City Cardiomyopathy Questionnaire. Improvement in functional status was assessed by New York Heart Association functional classification. Data was obtained at baseline and after 12-week follow-up. Data was compared using SPSS 26. Results: Of the 150 patients, 75(50%) were group A; 62(82.66%) males and 13(17.3%) females with mean age 63.76±10.05 years. There were 75(50%) patients in group B; 60(80%) males and 15(20%) females with mean age 66.13±11.73 years (p>0.05). The study was completed by 73(97.3%) in group A and 69(92%) in group B. The Kansas City Cardiomyopathy Questionnaire scores improved post-intervention compared to baseline values (p<0.001) in both groups. Group A showed comparatively greater improvement in health status compared to group B (p<0.05). Conclusions: Early initiation of dapagliflozin in patients admitted with acute heart failure was found to be associated with rapid and significant improvement in health and functional status. Clinical Trial Link: https://www.irct.ir. RCT No. (IRCT20220529055013N). Key Words: Heart failure, Dapagliflozin, HRQOL.